2000
DOI: 10.1002/(sici)1520-6300(200001/02)12:1<102::aid-ajhb12>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Can socioeconomic factors account for ?atypical? correlations between timing, peak velocity, and intensity of adolescent growth in Taiwanese girls?

Abstract: This study uses longitudinal height records of girls in two urban and one rural area in Taiwan. Individual height records were modeled with the Preece‐Baines Model 1 (PB1) function to test two related hypotheses: 1) Taiwanese students who experienced a relatively stable, affluent growth environment from an early age, as judged from parental education and stability of residence type, will have a pattern of correlations for the timing and intensity of the growth spurt similar to those of European and American fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Although the sequence of pubertal changes in adolescence is predictable, the timing of puberty is variable. Variations in pubertal timing depend on genetic and environmental factors [31]. In addition, secular trend appears to influence the physiological range in the timing of pubertal onset [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although the sequence of pubertal changes in adolescence is predictable, the timing of puberty is variable. Variations in pubertal timing depend on genetic and environmental factors [31]. In addition, secular trend appears to influence the physiological range in the timing of pubertal onset [32].…”
Section: Discussionmentioning
confidence: 99%
“…Two important premises, evaluated as part of the study, were that synergisms between under-nutrition and disease influenced the distribution of heights and BMI of first-graders to a significant extent in the less affluent Song Shan community, but very little among those in the more affluent setting. Although information on participants' dietary intakes and disease histories were not available, significant differences in the cost of housing, parental education levels, occupations, numbers of siblings, and growth parameters of other children in these two areas provided a basis for these assumptions initially (Floyd, 1998(Floyd, , 2000.…”
mentioning
confidence: 99%
“…A significant difference in the mean age at menarche between socioeconomic groups was noted in the surveyed group. However, the differences in stature increments in childhood and adolescence between those groups were very slight and statistically insignificant (Floyd, 2000). Still, despite the significant differences in age at menarche between socioeconomic groups, the increases in body height between the ages of 7 and 14 years, and 7 and 16, 17, 18 years, were similar in children from families of lower SES and families of high SES.…”
Section: Discussionmentioning
confidence: 78%
“…Many studies have shown that children from families of low socioeconomic status begin puberty at a late age, and reach each stage of development at an older age than children from families of high socioeconomic status (Obeidallah et al, 2000;Olszewska & Łaska-Mierzejewska, 2008;James-Todd et al, 2010). This may be due to different living conditions (Bogin et al, 1990;Floyd, 2000). Girls from families of low socioeconomic status had their first menstruation at an older age than their peers from families of high status.…”
Section: Discussionmentioning
confidence: 99%